2011
DOI: 10.1523/jneurosci.0435-11.2011
|View full text |Cite
|
Sign up to set email alerts
|

Asymmetric Inhibition of Ulk2 Causes Left-Right Differences in Habenular Neuropil Formation

Abstract: SUMMARY Studies of the zebrafish epithalamus have provided recent insights into the development of left-right brain asymmetry, which is crucial to normal human brain function. The habenular nuclei (Hb) of zebrafish are robustly asymmetric, with dense elaboration of neuropil only in the left lateral subnucleus. Because this feature is tightly correlated with asymmetric expression of K+ channel tetramerization domain-containing proteins 12.1 and 12.2 (Kctd12.1/12.2), we screened for Kctd12.1-interacting proteins… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
30
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 30 publications
4
30
0
Order By: Relevance
“…Analysis of the human and zebrafish KCTD proteins revealed that they are distinct from voltage-gated K ϩ channels, due to differences in their T1 domains and the absence of transmembrane domains (17,26,27). Our phylogenetic analysis based on the amino acid alignment of the T1 domains of all annotated human KCTD proteins and their orthologues revealed that they diverged deeply in time, preceding the split of animals from plants.…”
Section: Distinct Kctd Protein Domains Influence Desensitization Of Tmentioning
confidence: 87%
“…Analysis of the human and zebrafish KCTD proteins revealed that they are distinct from voltage-gated K ϩ channels, due to differences in their T1 domains and the absence of transmembrane domains (17,26,27). Our phylogenetic analysis based on the amino acid alignment of the T1 domains of all annotated human KCTD proteins and their orthologues revealed that they diverged deeply in time, preceding the split of animals from plants.…”
Section: Distinct Kctd Protein Domains Influence Desensitization Of Tmentioning
confidence: 87%
“…Various asymmetrically expressed factors, such as Kctd12.1, Kctd12.2, and Daam1a (dishevel associated activator of morphogenesis), have been associated with the growth of habenular neuropils while not apparently being required for the specification of habenular neuronal subtypes (30,157) (Table 1). In addition to dendritic extensions from habenular neurons, these neuropil domains contain afferent connections from pp cells to the left habenula (33) and from a subset of mitral cells of the olfactory bulb to the right habenula (74,116).…”
Section: Figurementioning
confidence: 99%
“…These proteins are known to be involved in different biological processes. For example, Ulk1 and Ulk2 are major regulators of autophagy (Ro et al, 2013); Ulk2 is reported to be involved in the development of some brain areas such as the habenula (Taylor et al, 2011); Ulk3 is involved in the regulation of the Sonic hedgehog signaling pathway (Maloverjan et al, 2010) that plays a crucial role in brain development (Fuccillo et al, 2006); moreover, deficiency of Stk36 or Ulk4 leads to a hydrocephalus-like phenotype (Merchant et al, 2005;Vogel et al, 2012). These data suggest that Ulk4 family members could be critical for the development and function of the nervous system.…”
Section: Introductionmentioning
confidence: 99%